Fabrication of 50 nm scale Pt nanostructures by block copolymer (BCP) and its characteristics of surface-enhanced Raman scattering (SERS). Issue 75 (26th July 2016) - Shin, Jae Hee; Kim, Hyun Gu; Baek, Gwang Min; Kim, Reehyang; Jeon, Suwan; Mun, Jeong Ho; Lee, Han-Bo-Ram; Jung, Yeon Sik; Kim, Sang Ouk; Kim, Kyoung Nam; Yeom, Geun Young
Abstract : Surface-enhanced Raman scattering (SERS) represents an important phenomenon that can solve the low signal intensity of Raman spectroscopy. In this study, we investigated the effect of various Pt nanostructures on the sensitivity of SERS. Abstract : Surface-enhanced Raman scattering (SERS) represents an important phenomenon that can solve the low signal intensity of Raman spectroscopy, applied as a bio and chemical sensor and analyzer. The SERS effect can be varied with the substrate structure. In this study, we investigated the effect of various Pt nanostructures ( e.g., Pt nanoholes, Pt nanorods, and Pt nanotubes) on the sensitivity of SERS. We fabricated 50 nm-scale Pt nanostructures with different heights with a self-aligned block copolymer (BCP) process composed of the self-assembly of BCP, Pt atomic layer deposition, and reactive ion etching of a silicon substrate and Pt. Our investigation of the SERS effect with rhodamine 6G showed a significant dependence on the shape (but not the height) of the nanostructure. Among the different Pt nanostructures investigated, Pt nanotubes (possessing the structural characteristics of nanoholes and nanorods) showed the highest SERS effect, while Pt nanoholes showed the lowest SERS effect.